Assessment And Comparison of Bacterial Contamination in Anterior Chamber Aspirates in Small Incision Cataract Surgery (SICS) And Phaco-Emulsification - Rahman, Mansur; Rahman, Mahbubur; Rahman, Farzana; Hossain, Mohammad; Islam, Shahidul (Journal of National Institute of Ophthalmology, 2023)
Introduction: The rate of occurrence of endophthalmitis after cataract surgery has been reduced to a greater extent now a day. Even then endophthalmitis related consequences are devastating. Several sources of infection, including contamination by air, solutions, surgical instruments, intraocular lens, and wound leakage have been identified. Aim of the Study: The study aimed to evaluate the influence of two methods of surgical technique of cataract surgery in bacterial as well as comparison of contamination by these two techniques. Methods: This prospective observational study was conducted over 60 patients with age related cataract in the department of Ophthalmology and Microbiology in Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh, from 1st January, 2009 to 30th June, 2009. Patients were selected purposively based on specific selection criteria. Selected patients underwent detail ophthalmic and systemic evaluation as well as relevant investigations. Cataract extraction followed by intraocular lens implantation was planned for all patients. The two techniques of cataract surgery such as SICS and Phacoemulsification were assigned to the patients randomly by 1:1 basis. 1 ml of anterior chamber contents were aspirated through aseptic technique by 26G needle from each patient pre-operatively, after capsulorrhexis (early per-operative) and just before wound closure by stromal hydration (late per-operative). All samples were sent for 10% KOH staining and culture and sensitivity test after proper leveling. Results: Micro-biological examination shows no sample was positive for 10% KOH staining. In SICS group, out of 30 samples 3 were found culture positive, which were positive in 4 and 5 samples in early per-operative and late per-operative sample respectively and in Phacoemulsification group, it was 2, 3, 5 pre-operative, early per-operative and late per-operative sample respectively. The common organisms isolated were Coagulase positive Streptococcus, Corynebacterium species, Streptococcus viridans, and Staphylococcus aureus etc. Almost none of the patients showed clinical activity except few cells and flare in the anterior chamber in early post-operative period. Conclusion: The microbiological examination shows the incidence of microbial contamination of anterior chamber contents is very low after cataract surgery by both form of technique, and there was no statistically significance difference in incidence between these two techniques. J.Natl.Inst.Ophthalmol.2023;6(1): 37-41